LEI DE HOOKE E O SISTEMA MASSA-MOLA: UMA APLICAÇÃO PRÁTICA COM OS ALUNOS DO 3º ANO DO ENSINO MÉDIO (REMUNOM, 2025)
This article aims to present an experimental and interdisciplinary approach to teaching Hooke's Law, through the construction and application of a mass-spring system in 3rd grade high school classes at a public school in Palmeirais-PI. The activity was structured in three pedagogical stages: theoretical foundation, practical experimentation with low-cost materials, and analysis of the data obtained. The experiment allowed students to empirically observe that the proportionality relationship between the applied force and the displacement of the mass depends on the elastic deformation of the spring, in addition to understanding the concept of elastic constant in the context of mathematical modeling with differential equations. The results demonstrate the potential of investigative practice in teaching Physics and Mathematics, promoting meaningful learning, critical thinking, and student protagonism, as proposed by the National Common Curricular Base. The proposal reinforces the importance of active and contextualized strategies for teaching fundamental concepts of science, favoring the articulation between theory and practice in the school environment.